New insights into the depressive mechanism of citric acid in the selective flotation of scheelite from fluorite. (1st September 2021) - Dong, Liuyang; Jiao, Fen; Qin, Wenqing; Wei, Qian
Highlights: Flotation separation of scheelite from fluorite was difficult. Depressant citric acid was introduced to depress fluorite in scheelite flotation. Citric acid was more adsorbed on fluorite surface in the form of CaL - . Stronger dissolution of fluorite surface occurred in the presence of citric acid. Flotation separation of scheelite from fluorite can be achieved with citric acid. Abstract: The effects of citric acid (CA) as a depressant in the separation of scheelite and fluorite were evaluated by microflotation test. The underlying selective separation mechanism was revealed via wetting analysis, Fourier transform infrared (FTIR) spectroscopy, thermodynamic calculations, adsorption amount tests, inductively coupled plasma–optical emission spectroscopy (ICP–OES) and atomic force microscopy (AFM). Microflotation tests showed that CA strongly depressed the flotation of fluorite but not of scheelite. Artificial mixed mineral separation tests showed that scheelite and fluorite achieved a good flotation separation effect in the presence of CA as the depressant. Mineral surface wettability analyses and adsorption amount tests indicated that CA was more strongly adsorbed onto the surface of fluorite than onto the surface of scheelite. FTIR spectroscopy proved that CA had a strong chemical adsorption on fluorite surface. Thermodynamic calculations indicated that CA could spontaneously form the organic complex CaL − on the surface of fluorite but not on the surface of scheelite. ICP–OES revealed that a strong dissolution behaviour occurred on the surface of fluorite that caused more calcium ions to dissolve into the slurry, thereby decreasing the number of adsorption sites of calcium ions on the surface of fluorite. AFM intuitively confirmed the intense adsorption and the strong dissolution behaviour of CA on the surface of fluorite.